2020
DOI: 10.1136/jitc-2020-001089
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes and biomarker analyses among patients with COVID-19 treated with interleukin 6 (IL-6) receptor antagonist sarilumab at a single institution in Italy

Abstract: BackgroundThe inflammatory pathology observed in severe COVID-19 disease caused by the 2019 novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is characterized by elevated serum levels of C reactive protein (CRP) and cytokines, including interferon gamma, interleukin 8 (IL-8), and interleukin 6 (IL-6). Initial reports from the outbreak in Italy, China and the USA have provided anecdotal evidence of improved outcomes with the administration of anti-IL-6 agents, and large-scale trials evaluating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 62 publications
2
63
0
2
Order By: Relevance
“…There are also elevated levels of pro-inflammatory cytokines, sometimes marked (a so-called cytokine storm). Convalescent plasma [236] and plasma exchange [237,238] improve survival rates in severe disease, and immunomodulatory therapies such as tocilizumab, a monoclonal antibody against the IL-6 receptor [239], and sarilumab, an IL-6 receptor antagonist [240], may offer protection and are currently undergoing clinical trials. Neutralising antibodies targeting other pro-inflammatory cytokines (IL-1, IL-17) may also offer protection, as too may potential inhibitors of complement system activation.…”
Section: Potential Upregulation Of Adam-17 In Covid-19mentioning
confidence: 99%
“…There are also elevated levels of pro-inflammatory cytokines, sometimes marked (a so-called cytokine storm). Convalescent plasma [236] and plasma exchange [237,238] improve survival rates in severe disease, and immunomodulatory therapies such as tocilizumab, a monoclonal antibody against the IL-6 receptor [239], and sarilumab, an IL-6 receptor antagonist [240], may offer protection and are currently undergoing clinical trials. Neutralising antibodies targeting other pro-inflammatory cytokines (IL-1, IL-17) may also offer protection, as too may potential inhibitors of complement system activation.…”
Section: Potential Upregulation Of Adam-17 In Covid-19mentioning
confidence: 99%
“…In addition, IL-6 blockade with tocilizumab does not impair the viral specific antibody responses despite of a delayed viral clearance driven by a higher initial viral load, indicating the safety of tocilizumab in patients with COVID-19 (82). Sarilumab is another kind of IL-6R blocker that is being investigated in SARS-CoV-2 infection (83, 84), which may reflect a possible clinical benefit regarding early intervention with IL-6-modulatory therapies for COVID-19 (85).…”
Section: Blocking Of Il-6/il-6rmentioning
confidence: 99%
“…In Montesarchio et al [62] retrospective case series of 15 patients with laboratory-confirmed SARS-CoV-2 infection, the oxygen saturation of patients at rest under the ambient air was equal or less than 93%, or they required oxygen therapy or mechanical ventilation. Twelve patients received a single SC injection of 400 mg sarilumab, and three received two doses within 24 hours.…”
Section: Sarilumab In Covid-19; Published Studiesmentioning
confidence: 99%
“…Timely administration of immunomodulatory drugs in covid-19 is a concern that should be taken into attention; for example, Wang et al [63] showed that early IFN-α 2b therapy reduced in-hospital mortality; whereas, late administration of IFN was associated with increased mortality and delayed recovery. Furthermore, it is important to note that all patients who died in Montesarchio et al [62] study were under invasive or noninvasive mechanical ventilation. Notably, patients who died or those nonresponsive to sarilumab had statistically higher baseline levels of IL-6 compared to those who did well, likely due to an advanced cytokine storm syndrome and suggesting that early intervention with sarilumab could prevent patients with COVID-19 from progressing to intensive care support.…”
Section: Sarilumab In Covid-19; Published Studiesmentioning
confidence: 99%